Silicon wafer cleaning with CF4/H2 plasma and its effect on the properties of dry thermally grown oxide - Chanana R.K.; Dwivedi R.; Srivastava S.K. (My University, 2025)
In the present study, a dry cleaning method for silicon wafers has been evaluated using CF4/50% H2 plasma followed by exposure to O2 and H2 plasmas separately. The effect of the cleaning process and the exposure to these plasmas on the interface trap level density, fixed oxide charge density, and flat band voltage has been investigated. It has been found that the cleaning method including the O2 plasma exposure gives low values of these parameters, which are also low when compared to the values obtained for MOS devices fabricated after the conventional wet chemical cleaning process prevalent in the microelectronic industries. The proposed cleaning process eliminates the regrowth of native oxide which is unavoidable in the wet chemical cleaning process. © 1992.